Eric McLuhan, Marshall McLuhan, Walter Ong, and Connection Consciousness - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
In this article, I highlight the lives and works of three distinguished media ecology theorists: (1) Eric McLuhan (1942-2018; Ph.D. in English, University of Dallas, 1982); (2) Marshall McLuhan (1911-1980; Ph.D. in English, Cambridge University, 1943); and(3) Walter J. Ong, S.J. (1912-2003; Ph.D. in English, Harvard University, 1955). Throughout this article, I use Eric McLuhan’s 2015 book The Sensus Communis, Synesthesia, and the Soul: An Odyssey as a touchstone for my discussion of connection consciousness. I round off this article by listing a wide range of other books and articles that are also related to connection consciousness.